Instructional Videos to Familiarize Young Autistic Adults With Grocery Tasks With a View to Vocational Integration: From Design to Practicability. - Bertrand-Ouellet, J.; Vincent, C.; Julien-Gauthier, F.; Dumont, F.; Desmarais, C.; Lecours, A.; Poulin, V.; Kiss, J.; Hu, T.; Blouin, L. (Journal of Vocational Rehabilitation, 2025)
Background: Young adults with autism spectrum disorder (ASD) face challenges in obtaining employment. Objective: To test the practicality and feasibility of using instructional videos in a community organization involved in vocational rehabilitation and work integration for people with autism. Methods: Three methodological steps were achieved: 'Research-development', iterative content validation and practicability study. Eleven employees of a grocery store were filmed performing tasks in seven departments. Each video was followed by questions. Four validation phases were carried out with different groups of stakeholders (n = 25). Four autistic youth in a work training organization had tested successfully 6 to 9 instructional videos. Results: A man of 26 years old was positive for 6 videos and negative about 3 tasks (Wrapping cheese, Placement of Products in the charcuterie section, Sous-vide). He had no discomfort 67% of the time. What bothers him often were the smell, social contacts and the texture. Twenty-one instructional videos from 2 to 6 min cover fish section(n = 5), fruits and vegetables(n = 2), cash register(n = 2), grocery store display(n = 2), bakery(n = 3), cheese and charcuterie(n = 4) and ready-to-eat(n = 3). Conclusion: Education, orientation and job placement service, rehabilitation and community stakeholders can use the response to the questions to target socio-professional interests while providing a space for discussion about future integration into grocery store work.